HUBUNGAN KECEPATAN LARI ZIG-ZAG DENGAN KEMAMPUAN MENGGIRING BOLA PADA PERMAINAN SEPAK BOLA - Badaruddin, Badaruddin (Fakultas Ilmu Keolahragaan Unimed, 2024)
This research aims to determine the relationship between zigzag running speed and ball dribbling ability in soccer games. This research was conducted at SMA Negeri 2 Tomia, Wakatobi Regency, Southeast Sulawesi using a survey method. The instrument used to determine the independent variable was a zig-zag running speed test using a slalom test with the running speed changing direction over a pile, while to determine the dependent variable a ball dribbling test over obstacles was used. The research data was analyzed using product moment correlation statistics with a significance level of 0.05. The results of the research show that there is a positive relationship between zig-zag running speed and dribbling ability in soccer games, where Rxy = 0.62 > F table (0.5:40) = 0.304